Building Religious Tolerance Through Character Education Based on Local Wisdom of Bugis Culture - Yunus (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This study focuses on the issue of the relevance of Bugis culture in creating a tolerant religious community through character education. This is nothing but a contribution to religious tolerance which has recently been eroded due to primordial issues, ethnicity and so on. This research is an qualitative research with ethnography approach. Overall, the authors note that local wisdom of Bugis culture is quite effective, this can be seen in the application inside the classroom and outside the classroom and not an obstacle to creating a tolerant religious community. The local wisdom held in the Bugis culture above in fact has the values of empathy, compassion, togetherness, respect for differences, willing to sacrifice, giving opportunities to others and being patient in acting. In addition, the local wisdom that is cultivated by the Palopo Community, especially the Bugis, when used as the basis for developing character education in universities is in line with the plurality values that characterize this nation. Thus, local wisdom can make universities more characterized and at the forefront in promoting cultural values for progress and development at the national and international levels.